Inducible Clindamycin Resistance and Biofilm Production among Staphylococci Isolated from Tertiary Care Hospitals in Nepal - Sarita Manandhar; Raju Shrestha; Ratna Shova Tuladhar; Sunil Lekhak (MDPI AG, 2021)
Resistance to antibiotics, biofilm formation and the presence of virulence factors play important roles in increased mortality associated with infection by staphylococci. The macrolide lincosamide streptogramin B (MLSB) family of antibiotics is commonly used to treat infections by methicillin-resistant isolates. Clinical failure of clindamycin therapy has been reported due to multiple mechanisms that confer resistance to MLSB. This study aims to find the incidence of different phenotypes of MLSB resistance and biofilm production among staphylococci. A total of 375 staphylococci were isolated from different clinical samples, received from two tertiary care hospitals in Nepal. Methicillin resistance was detected by cefoxitin disc diffusion method and inducible clindamycin resistance by D test, according to CLSI guidelines. Biofilm formation was detected by the tissue culture plate method and PCR was used to detect ica genes. Of the total staphylococci isolates, 161 (42.9%) were Staphylococcus aureus, with 131 (81.4%) methicillin-resistant strains, and 214 (57.1%) isolates were coagulase-negative staphylococci, with 143 (66.8%) methicillin-resistant strains. The overall prevalence of constitutive MLSB (cMLSB) and inducible MLSB (iMLSB) phenotypes was 77 (20.5%) and 87 (23.2%), respectively. Both iMLSB and cMLSB phenotypes predominated in methicillin-resistant isolates. The tissue culture plate method detected biofilm formation in 174 (46.4%) isolates and ica genes in 86 (22.9%) isolates. Among biofilm producing isolates, cMLSB and iMLSB phenotypes were 35 (20.1%) and 27 (15.5%), respectively. The cMLSB and iMLSB were 11 (12.8%) and 19 (22.1%), respectively, in isolates possessing ica genes. Clindamycin resistance in the form of cMLSB and iMLSB, especially among MRSA, emphasizes the need for routine D tests to be performed in the lab.